MANFAAT DAN POTENSI PASAR KREMPYENG BAGI PEREKONOMIAN MASYARAKAT - Roihatul Janah (Scimadly Publishing, 2023)
The krampyeng market is one of the traditional markets in Indonesia. The krampyeng market is usually located on the side of the road in a fairly crowded place and the krampyeng market is usually open from early in the morning. This study aims to determine the benefits and potential of the existing krampyeng market. This research uses a descriptive qualitative research type. Data collection techniques using literature, interviews, and observation. The results of this study indicate that the krampyeng market has several benefits for the community, including easy access to shop for daily necessities, opening up jobs, becoming more famous and bustling in the area, becoming a distinct advantage for the region, being able to increase income, and so on. Meanwhile, the potential for the Krempyeng market is in the form of cheap product prices, varied products, jobs, helping people's income, strategic timing and location, and other supporting factors such as supervision from the government.